2019
DOI: 10.1111/josh.12839
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Burnout and Contextual and Compositional Elements of School Environment

Abstract: BACKGROUND: Teachers report higher levels of stress than most occupational groups. Burnout is a specific psychological condition that results from chronic job stress characterized by emotional exhaustion, low personal accomplishment, and depersonalization. This study considers associations between aspects of the school environment and teacher burnout.METHODS: Exploratory analysis of baseline data from a cluster randomized controlled trial of 40 schools and 2278 teachers in the United Kingdom. Multilevel method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 51 publications
3
29
0
2
Order By: Relevance
“…The emotional exhaustion of teachers is associated with high turnover rates and lower quality teaching, which impacts student participation and performance. The promotion of the school's organizational health, personal selfconfidence, affiliation with colleagues, and having more resources academically, such as preventive interventions, are associated with less stress and exhaustion [2,3]. In a study developed by Alvites-Huamaní [4] on teaching stress and psychosocial factors in basic and higher education teachers in Latin America, North America, and Europe, a significant positive correlation was found between stress and psychosocial factors such as workplace conditions, workload, content and characteristics of duty, academic role and career development, social interaction, and organizational aspects.…”
Section: Introductionmentioning
confidence: 99%
“…The emotional exhaustion of teachers is associated with high turnover rates and lower quality teaching, which impacts student participation and performance. The promotion of the school's organizational health, personal selfconfidence, affiliation with colleagues, and having more resources academically, such as preventive interventions, are associated with less stress and exhaustion [2,3]. In a study developed by Alvites-Huamaní [4] on teaching stress and psychosocial factors in basic and higher education teachers in Latin America, North America, and Europe, a significant positive correlation was found between stress and psychosocial factors such as workplace conditions, workload, content and characteristics of duty, academic role and career development, social interaction, and organizational aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies (Lim & Eo, 2014;McCarthy et al, 2009;McCormick & Barnett, 2011;Ullrich et al, 2012;Van Maele & Van Houtte, 2015) chose not to include school-level variables when the ICC was considered too low or if the school-level variance component was not significant. Clearly, the level at which some studies (Lim & Eo, 2014;McCarthy et al, 2009;McCormick & Barnett, 2011) deem the ICC too low to include school-level variables or to use multilevel analysis is considered acceptable in other studies (Ford et al, 2019;González-Morales et al, 2011;Klusmann et al, 2008;O'Brennan et al, 2017;Pas et al, 2012;Shackleton et al, 2019). There is no consensus in the literature as to what level of ICC is suitable to warrant using multilevel analysis or to include school-level variables (Hox et al, 2017).…”
Section: Is Teacher Burnout Related To the School Context?mentioning
confidence: 99%
“…Four of these studies (Ford et al, 2019;Klusmann et al, 2008;O'Brennan et al, 2017;Pas et al, 2012) reported standardized coefficients for the schoollevel variables. Eight studies (Ford et al, 2019;González-Morales et al, 2011;Kim et al, 2017;Klusmann et al, 2008;O'Brennan et al, 2017;Ross et al, 2012;Shackleton et al, 2019;Zheng et al, 2017) found significant relationships between school-level variables and a burnout measure, but only three of them (Klusmann et al, 2008;O'Brennan et al, 2017;Zheng et al, 2017) included a measure for the effect size of the school-level variable. The relationship between the coefficients of school-level variables and teacher burnout is discussed in the summary of studies in the supplemental appendix (available on the journal website).…”
Section: Is Teacher Burnout Related To the School Context?mentioning
confidence: 99%
“…Recognizing the multiple roles played by teachers in rural contexts, including instrumental roles in promoting positive classroom and school climates, 32,47 efforts to build staff capacity and attend to staff well‐being is critical 48 . Indeed, the relationship between teacher burnout and school climate is likely bidirectional, with teachers serving a core role in engaging students and families but teacher burnout also predicted by poorer school climate 49 . In the face of new challenges brought about by the COVID‐19 pandemic, which have likely decreased student engagement and increased teacher stress, 50,51 appropriately supporting educators' own well‐being will be critical in both ensuring a healthy and supportive school climate, and in combating personnel challenges experienced in rural schools.…”
Section: Implications For School Health and Equitymentioning
confidence: 99%